Planting Media Composition Drives Vegetative Establishment and Biomass Accumulation of Grapevine Stem Cuttings under Tropical Nursery Conditions - Wisnaningsih; Moh Haris Imron S Jaya (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
The success of grapevine (Vitis vinifera L.) propagation through stem cuttings is strongly influenced by planting media quality during the nursery stage. Under tropical lowland conditions, unstable root-zone environments often reduce seedling vigor and biomass accumulation. Therefore, suitable manure-based media are needed to improve vegetative establishment and nursery efficiency. This study aimed to evaluate the effects of different manure-based planting media on vegetative growth and biomass accumulation of grapevine stem cuttings under tropical screen-house conditions in Bandar Lampung, Indonesia. The experiment was arranged in a randomized complete block design consisting of four treatments: M1 = sand + soil (1:1), M2 = sand + soil + cattle manure (1:1:1), M3 = sand + soil + goat manure (1:1:1), and M4 = sand + soil + chicken manure (1:1:1), with six replications. The results showed that the cattle manure-based medium consistently produced the best vegetative performance, increasing shoot length, leaf number, leaf area, fresh weight, and dry weight by 67.6%, 83.3%, 83.1%, 38.5%, and 40.4%, respectively, compared with the control treatment. Overall, cattle manure-based media provided the most favorable conditions for vegetative establishment and biomass accumulation of grapevine stem cuttings under tropical nursery conditions.